Invasive tracheobronchial aspergillosis developed during radioimmunotherapy for malignant lymphoma. Issue 4 (4th March 2018) - Sato, Shuku; Tamai, Yotaro; Sugimoto, Hideyasu; Watanabe, Shinji; Kumagae, Tomohiro; Kannbe, Emiko; Tanaka, Eri
Key Clinical Message: Invasive pulmonary aspergillosis (IPA) often occurs during the treatment of malignant lymphoma. However, invasive tracheobronchial aspergillosis (ITBA) is a rare form of IPA. Particularly, due to the decrease in immunity associated with chemotherapy, it is difficult to diagnose ITBA only by CT imaging and serological findings. Pathologic diagnosis by bronchoscopy is important. Abstract : Invasive pulmonary aspergillosis (IPA) often occurs during the treatment of malignant lymphoma. However, invasive tracheobronchial aspergillosis (ITBA) is a rare form of IPA. Particularly, due to the decrease in immunity associated with chemotherapy, it is difficult to diagnose ITBA only by CT imaging and serological findings. Pathologic diagnosis by bronchoscopy is important.